The Role Of Social Media In Shaping Adolescent Prosocial Behavior - Arfian; Ardina Aulia Sari; Fatihamah; Radita Silviyana; Restu Paramasasta (Insight School Academy, 2024)
Introduction to The Problem : Social media is increasingly needed in everyday life for communication activities, socialization, and social media can't be denied has a huge influence on teenagers. Purpose : The aim of this study is to study the impact of social media on adolescent prosocial behavior. Design/methods/approach : This research data is collected using the method of literature study or also known as library research. Data is analyzed discreetly to the content of the data that has been collected. Findings : The results show the positive and negative impact of social media content on improved prosocial behavior. Research implications/limitations : This study is too general, not specific to a particular subject, such as a junior high school or a junior junior, so the conclusions of the study are generic. Originality/value : The study concluded that social media, if used properly, would be an effective tool for raising social awareness and concern among teenagers.